Effect of the Cognitive-Behavioral Prevention Program on Levels of Depression Symptoms Among Working Adolescents in Turkey - BAYRI BİNGÖL, FADİME (SLACK INC, 2016)
The current study was conducted to determine the effect of the Cognitive-Behavioral Prevention Program (CBPP) on levels of depression symptoms, ability to cope with stress, and automatic negative thought patterns among working adolescents in Turkey. The CBPP was conducted once per week for eight sessions and then once per month for six sessions. Data were collected using the Beck Depression Inventory, Automatic Thoughts Questionnaire, and Rosenbaum's Learned Resourcefulness Schedule. Observations were made prior to administration of the CBPP, upon conclusion of the program, and at 6 and 12 months. Chi-square and t tests were used for data analysis. Mean age of participants was 15.85, and they worked a mean 10.84 hours per day. After taking part in the CBPP, participants displayed a decrease in levels of depression symptoms, an increase in their ability to cope with stress, and diminished automatic negative thoughts (all p = 0.001), thus indicating that they benefited from the program and its effectiveness continued through 12-month follow up.
Keywords: MENTAL-HEALTH; STRESS; SCHOOL; THERAPY; TRIAL; BRAIN